An ultra‐wide band diversity antenna with band‐rejection capability for imaging applications. Issue 7 (16th May 2017) - Latif, Farah; Tahir, Farooq A.; Khan, Muhammad U.; Sharawi, Mohammad S.
Abstract: In this paper, a 2‐element UWB‐MIMO antenna system is proposed for imaging applications. Each antenna element consists of semi‐circular slot excited by 50 Ω microstrip transmission lines. Two small stubs are used on both sides of the microstrip lines for better impedance matching at higher frequencies. The band‐rejection at WLAN (5.15–5.825 GHz) band is achieved through a U‐shaped slot in the feeding transmission line. The antenna works efficiently from 3.1 to 10.6 GHz, covering the entire standard UWB. Slots in the ground plane are introduced to improve the isolation level between the antenna elements. A minimum isolation of 20 dB is attained in the entire operating band. The proposed antenna has a size of 58 × 27 m m 2 . Good agreement is obtained between simulated and measured results for reflection coefficient, isolation and consistent radiation patterns over the entire operating band that makes it promising candidate for medical imaging application in UWB.